Chest physiotherapy is not clinically indicated for infants receiving outpatient care for acute wheezing episodes. (10th March 2014) - Castro‐Rodriguez, Jose A.; Silva, Rodrigo; Tapia, Patricio; Salinas, Pamela; Tellez, Alvaro; Leisewitz, Thomas; Sanchez, Ignacio
Abstract Aim To evaluate the effectiveness of chest physiotherapy (CPT), which provides slow and long expiratory flow and assisted cough techniques, in infants receiving outpatient care for acute wheezing episodes. Methods Forty‐eight infants with moderate acute wheezing episodes were randomised to receive either salbutamol MDI with CPT (n = 25) or without CPT (n = 23). The clinical score and SpO2 levels were recorded, before and after treatment, in a blinded design. The primary outcome was discharge after the first hour of treatment: clinical score ≤5/12 and SpO2 ≥ 93%. Secondary outcomes were the number of admissions to hospital after the second hour, use of oral corticosteroid bursts and admissions to hospital on day seven. Results There were no differences between children with and without CPT in discharge rate (92% vs. 87%), clinical score (median [IQR]: 2.8 [2.2–3.3] vs. 3.4 [2.8–4.1]) and SpO2= (96.4 [95.7–97.1] vs. 96.0 [94.9–96.5]) after the first hour of treatment or in the number of hospital admissions after the second hour. No differences were observed at days seven and 28 following treatment. Conclusion There was no evidence of clinical benefits from these specific CPT techniques for infants receiving outpatient care for acute wheezing episodes.